Analisis Penyelesaian KDRT Secara Damai dalam Perspektif Viktimologi : Studi Kasus Korban KDRT di Kota Serang - Solihat Solihat; Farah Malika Syahda; Nathania Nathania; Syarifah Azsefira Adhela; Helpi Helpi; Anindya Pratiwi (Hukum Inovatif : Jurnal Ilmu Hukum Sosial dan Humaniora, 2025)
Domestic violence is a human rights violation that still occurs frequently in Indonesia, despite being regulated in Law No. 23/2004 on the Elimination of Domestic Violence. Many victims, especially women, choose to resolve domestic violence cases peacefully due to various factors such as social pressure, economic dependence, and community stigma. This research aims to analyze the factors behind the victim's decision to choose an amicable settlement and evaluate the mechanism from a victimology perspective. The research methodology uses an empirical juridical approach with primary data collection through interviews with victims of domestic violence in Serang City and secondary data from legal documents and related literature. The results show that the decision to reconcile is influenced by the presence of children in the household, economic independence, fear, and family or other people. In addition, efforts that can be made to ensure the prevention of recurrence of domestic violence are with temporary protection regulated in Article 16 of the PKDRT Law. The contribution of this research lies in an in-depth understanding of the dynamics of peaceful settlements in domestic violence cases and victimology-based policy recommendations to improve victim protection. This research also encourages the application of a restorative justice approach that favors the psychosocial needs of victims and the prevention of repeated violence.